Chip structure of GaN-based high-power blue laser

By plating multi-layer anti-reflection layer and high-reflection layer in the chip structure of GaN-based high-power blue light laser, the problem of optical catastrophe at high power is solved, and the reliability and photoelectric conversion efficiency of the laser are improved.

CN119171180AInactive Publication Date: 2024-12-20GEN SEMICONDUCTOR (ANHUI) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411304635.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2024-12-20
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

GaN-based high-power blue light lasers are prone to optical catastrophic damage and death of lamps due to high reflective layers at high power, reducing reliability.

Method used

In the chip structure of GaN-based high-power blue light laser, the cavity surfaces on both sides of the epitaxial layer are coated with anti-reflection layers and high-reflection layers respectively. The anti-reflection layer includes a multi-layer sub-reflection layer, and the electric field intensity that simulates the light field distribution has multiple electric field strengths. peaks and valleys are used to reduce laser power density and photon density and reduce optical catastrophe risk.

Benefits of technology

It reduces the optical catastrophe chance of the laser, improves the optical catastrophe current, reduces the threshold current, and improves the photoelectric conversion efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119171180A_ABST
    Figure CN119171180A_ABST
Patent Text Reader

Abstract

The GaN-based high-power blue laser chip structure comprises a substrate and an epitaxial layer, the epitaxial layer is arranged on the upper layer of the substrate, the surface of a first cavity surface of the epitaxial layer is plated with an antireflection layer, and the surface of a second cavity surface of the epitaxial layer is plated with a high-reflection layer. The anti-reflection layer comprises a first sub-anti-reflection layer, a second sub-anti-reflection layer and a third sub-anti-reflection layer which are sequentially plated on the surface of the first cavity surface, and the electric field intensities of simulation light field distribution of the epitaxial layer and the anti-reflection layer have a plurality of peak electric field intensities and a plurality of valley electric field intensities. The threshold current of the laser can be reduced, and the photoelectric conversion efficiency of the laser is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of semiconductor optoelectronic devices, and in particular to a chip structure of a GaN-based high-power blue laser. Background Art

[0002] Lasers are widely used in laser display, laser TV, laser projector, communication, medical treatment, weapons, guidance, ranging, spectral analysis, cutting, precision welding, high-density optical storage and other fields. There are many types of lasers, and the classification methods are also diverse, mainly including solid, gas, liquid, semiconductor and dye types of lasers; compared with other types of lasers, all-solid-state semiconductor lasers have the advantages of small size, high efficiency, light weight, good stability, long life, simple and compact structure, and miniaturization.

[0003] There are big differences between lasers and nitride semiconductor light-emitting diodes:

[0004] 1) Laser is generated by stimulated radiation of carriers, the spectrum half-width is small, the brightness is very high, and the output power of a single laser can be in the W level, while nitride semiconductor light-emitting diodes are spontaneously radiated, and the output power of a single light-emitting diode is in the mW level;

[0005] 2) The current density of the laser reaches KA / cm2, which is more than 2 orders of magnitude higher than that of nitride light-emitting diodes, resulting in stronger electron leakage, more serious Auger recombination, stronger polarization effect, more serious electron-hole mismatch, and more serious efficiency attenuation Droop effect;

[0006] 3) The spontaneous transition radiation of the light-emitting diode is incoherent light that transitions from a high energy level to a low energy level without any external influence, while the laser is stimulated transition radiation, and the energy of the induced photon should be equal to the difference in the energy level of the electron transition, producing the same coherent light as the photon and the induced photon;

[0007] 4) Different principles: When an external voltage is applied to a light-emitting diode, electron holes jump to a quantum well or a pn junction to generate radiative recombination light, while a laser can only emit when the lasing conditions are met. The carrier distribution in the active region must be reversed, and the stimulated radiation light oscillates back and forth in the resonant cavity. The propagation in the gain medium amplifies the light, and the threshold condition is met so that the gain is greater than the loss, and finally the laser is output.

[0008] Nitride semiconductor lasers have the following problems: low-power blue or green single-mode lasers have low energy (generally 5 to 200 mW), and the reflectivity of the anti-reflection layer AR can be set at a high level of 65 to 95%, so that the stimulated radiation oscillating in the laser cavity surface is stronger, so that the carriers in the active layer can accelerate the distribution reversal, reduce the threshold of the laser, and improve the slope efficiency. However, high-power multi-mode blue lasers have high power (generally 2 to 15 W), and the power density of the laser cavity surface is high. If the reflectivity of the anti-reflection layer is set to 65 to 95%, the laser power in the laser reflection cavity will be too high, and the laser power emitted will be less, so that the laser cavity surface will be subjected to a large laser power, which is easy to cause optical catastrophic damage and dead lamps, burst tubes and other problems, resulting in reduced reliability. Summary of the invention

[0009] In order to solve one of the above technical problems, the present invention provides a chip structure of a GaN-based high-power blue laser.

[0010] The embodiment of the present invention provides a chip structure of a GaN-based high-power blue laser, comprising a substrate and an epitaxial layer, wherein the epitaxial layer is arranged on the upper layer of the substrate, and the left and right sides of the epitaxial layer are respectively a first cavity surface and a second cavity surface, and the first cavity surface is located at the far end of the laser emission direction, and the second cavity surface is located at the near end of the laser emission direction, an anti-reflection layer is plated on the surface of the first cavity surface, and a high-reflection layer is plated on the surface of the second cavity surface, and the anti-reflection layer comprises a first sub-anti-reflection layer, a second sub-anti-reflection layer and a third sub-anti-reflection layer which are sequentially plated on the surface of the first cavity surface, and the electric field strength of the simulated optical field distribution of the epitaxial layer and the anti-reflection layer has multiple peak electric field strengths and multiple valley electric field strengths;

[0011] The first peak electric field intensity is located in the epitaxial layer, the second peak electric field intensity is located in the interface region between the first cavity surface and the first sub-anti-reflection layer, the third peak electric field intensity is located in the interface region between the second sub-anti-reflection layer and the third sub-anti-reflection layer, the intensity ratio of the first peak electric field intensity to the second peak electric field intensity is 0.8 to 1.2, and the intensity ratio of the second peak electric field intensity to the third peak electric field intensity is 0.8 to 1.2;

[0012] The first valley electric field strength is located in the epitaxial layer, the second valley electric field strength is located in the first sub-anti-reflection layer, and the intensity ratio of the first valley electric field strength to the second valley electric field strength is 0.2 to 0.8.

[0013] Preferably, the reflectivity of the anti-reflection layer at a laser wavelength of 450 nm is 15% to 30%, and the reflectivity of the high-reflection layer at a laser wavelength of 450 nm is 95% to 100%.

[0014] Preferably, the first sub-anti-reflection layer is any one of Al2O3, AlN / Al2O3 or AlON / Al2O3, the second sub-anti-reflection layer is Ta2O5 or SiO2, and the third sub-anti-reflection layer is Ta2O5 or SiO2.

[0015] Preferably, when the first sub-anti-reflection layer is Al2O3, the quarter wavelength of the first sub-anti-reflection layer is 1.8 to 2.2, the quarter wavelength of the second sub-anti-reflection layer is 0.01 to 0.2, and the quarter wavelength of the third sub-anti-reflection layer is 0.01 to 0.2;

[0016] When the first sub-anti-reflection layer is AlN / Al2O3 or AlON / Al2O3, the quarter wavelength of AlN or AlON of the first sub-anti-reflection layer is 0.1 to 0.3, the quarter wavelength of Al2O3 of the first sub-anti-reflection layer is 1.4 to 1.8, the quarter wavelength of the second sub-anti-reflection layer is 0.1 to 0.3, and the quarter wavelength of the third sub-anti-reflection layer is 0.1 to 0.3.

[0017] Preferably, when the first sub-anti-reflection layer is Al2O3, the ratio of a quarter wavelength of the first sub-anti-reflection layer to a quarter wavelength of the second sub-anti-reflection layer is 20 to 40, the ratio of a quarter wavelength of the first sub-anti-reflection layer to a quarter wavelength of the third sub-anti-reflection layer is 20 to 40, and the ratio of a quarter wavelength of the second sub-anti-reflection layer to a quarter wavelength of the third sub-anti-reflection layer is 0.5 to 1.5;

[0018] When the first sub-anti-reflection layer is AlN / Al2O3 or AlON / Al2O3, the ratio of one-quarter wavelength of Al2O3 in the first sub-anti-reflection layer to one-quarter wavelength of the first sub-anti-reflection layer is 3 to 20, the ratio of one-quarter wavelength of Al2O3 in the first sub-anti-reflection layer to one-quarter wavelength of the second sub-anti-reflection layer is 5 to 20, the ratio of one-quarter wavelength of Al2O3 in the first sub-anti-reflection layer to one-quarter wavelength of the third sub-anti-reflection layer is 5 to 20, and the ratio of one-quarter wavelength of the second sub-anti-reflection layer to one-quarter wavelength of the third sub-anti-reflection layer is 1 to 3.

[0019] Preferably, when the first sub-anti-reflection layer is Al2O3, the thickness of the first sub-anti-reflection layer is 100nm to 200nm, the thickness of the second sub-anti-reflection layer is 1nm to 20nm, and the thickness of the third sub-anti-reflection layer is 1nm to 20nm;

[0020] When the first sub-anti-reflection layer is AlN / Al2O3 or AlON / Al2O3, the thickness of Al2O3 of the first sub-anti-reflection layer is 80nm to 150nm, the thickness of AlN or AlON of the first sub-anti-reflection layer is 5nm to 50nm, the thickness of the second sub-anti-reflection layer is 1nm to 20nm, and the thickness of the third sub-anti-reflection layer is 1nm to 20nm.

[0021] Preferably, when the first sub-anti-reflection layer is Al2O3, the ratio of the thickness of the first sub-anti-reflection layer to the thickness of the second sub-anti-reflection layer is 20 to 50, the ratio of the thickness of the first sub-anti-reflection layer to the thickness of the third sub-anti-reflection layer is 20 to 50, and the ratio of the thickness of the second sub-anti-reflection layer to the thickness of the third sub-anti-reflection layer is 0.8 to 2.0;

[0022] When the first sub-anti-reflection layer is AlN / Al2O3 or AlON / Al2O3, the ratio of the thickness of Al2O3 in the first sub-anti-reflection layer to the thickness of the first sub-anti-reflection layer AlN or AlON is 5 to 20, the ratio of the thickness of Al2O3 in the first sub-anti-reflection layer to the thickness of the second sub-anti-reflection layer is 5 to 20, the ratio of the thickness of Al2O3 in the first sub-anti-reflection layer to the thickness of the third sub-anti-reflection layer is 5 to 20, and the ratio of the thickness of the second sub-anti-reflection layer to the thickness of the third sub-anti-reflection layer is 0.8 to 2.0.

[0023] Preferably, the electric field strength of the epitaxial layer and the anti-reflection layer has a sine or cosine function distribution.

[0024] Preferably, the outer layer of the third sub-anti-reflection layer is further plated with a fourth sub-anti-reflection layer, and the fourth sub-anti-reflection layer has the same structure and composition as the second sub-anti-reflection layer;

[0025] Alternatively, the outer layer of the third sub-anti-reflection layer is also sequentially plated with a fourth sub-anti-reflection layer and a fifth sub-anti-reflection layer, the fourth sub-anti-reflection layer has the same structural composition as the second sub-anti-reflection layer, and the fifth sub-anti-reflection layer has the same structural composition as the third sub-anti-reflection layer.

[0026] Preferably, the epitaxial layer includes a lower confinement layer, a lower waveguide layer, an active layer, an upper waveguide layer, an electron blocking layer and an upper confinement layer, which are arranged in sequence from bottom to top, and the epitaxial layer is any one or any combination of GaN, InGaN, InN, AlInN, AlGaN, AlInGaN, AlN, GaAs, GaP, InP, AlGaAs, AlInGaAs, AlGaInP, InGaAs, InGaAsN, AlInAs, AlInP, AlGaP, InGaP, GaSb, InSb, InAs, InAsSb, AlGaSb, AlSb, InGaSb, AlGaAsSb, InGaAsSb, SiC, Ga2O3, BN, and diamond.

[0027] Preferably, the substrate comprises sapphire, silicon, Ge, SiC, AlN, GaN, GaAs, InP, InAs, GaSb, sapphire / SiO2 composite substrate, Mo, TiW, CuW, Cu, sapphire / AlN composite substrate, diamond, graphene, sapphire / SiN x , Sapphire / SiO2 / SiN x Composite substrate, sapphire / SiN x Any one of a / SiO2 composite substrate, a magnesium aluminum spinel MgAl2O4, MgO, ZnO, ZrB2, LiAlO2 and LiGaO2 composite substrate.

[0028] The beneficial effects of the present invention are as follows: the present invention is provided with an anti-reflection layer and a high-reflection layer on the cavity surfaces of both sides of the epitaxial layer of the chip structure of the GaN-based high-power blue laser. The anti-reflection layer includes a first sub-anti-reflection layer, a second sub-anti-reflection layer and a third sub-anti-reflection layer sequentially plated on the surface of the first cavity surface, and the electric field intensity of the simulated light field distribution of the epitaxial layer and the anti-reflection layer has multiple peak electric field intensities and multiple valley electric field intensities, thereby reducing the laser power density of the anti-reflection layer of the high-power blue laser, reducing the high photon density borne by the anti-reflection layer and the high-reflection layer of the laser, reducing the optical catastrophe probability of the laser, and improving the optical catastrophe current; at the same time, the radiation intensity in the resonant cavity formed by the anti-reflection layer and the high-reflection layer of the laser decreases, reducing the photon density, and can also reduce the carrier absorption loss of the conduction band and valence band carrier concentration of the active layer, reduce the light absorption loss of impurity defects and Auger recombination, inhibit Fermi level drift, improve the problem of reducing the state density of particle number inversion, thereby reducing the threshold current of the laser and improving the photoelectric conversion efficiency of the laser. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0030] Figure 1 A schematic diagram of the chip structure of a GaN-based high-power blue laser according to an embodiment of the present invention;

[0031] Figure 2 Schematic diagram of the structure of the anti-reflection layer according to an embodiment of the present invention, with 3 layers;

[0032] Figure 3 This is an electric field intensity distribution diagram of a simulated light field distribution of a chip structure of a GaN-based high-power blue laser according to an embodiment of the present invention, wherein the first sub-anti-reflection layer is Al2O3;

[0033] Figure 4 The electric field intensity distribution diagram of the simulated light field distribution of the chip structure of the GaN-based high-power blue laser according to the embodiment of the present invention, wherein the first sub-antireflection layer is AlN / Al2O3 or AlON / Al2O3;

[0034] Figure 5 This is a reflectivity diagram of a simulated light field distribution of a chip structure of a GaN-based high-power blue laser according to an embodiment of the present invention, wherein the first sub-antireflection layer is Al2O3;

[0035] Figure 6 A reflectivity diagram of a simulated light field distribution of a chip structure of a GaN-based high-power blue laser according to an embodiment of the present invention, wherein the first sub-antireflection layer is AlN / Al2O3 or AlON / Al2O3;

[0036] Figure 7 Schematic diagram of the structure of the anti-reflection layer according to an embodiment of the present invention, with 4 layers;

[0037] Figure 8 Schematic diagram of the structure of the anti-reflection layer according to an embodiment of the present invention, with 5 layers;

[0038] Fig. 9 It is a schematic diagram of the structure of the epitaxial layer described in an embodiment of the present invention.

[0039] Reference numerals:

[0040] 100, substrate, 101, epitaxial layer, 102, anti-reflection layer, 103, high reflection layer;

[0041] 1011, first cavity surface, 1012, second cavity surface;

[0042] 1021, a first sub-anti-reflection layer, 1022, a second sub-anti-reflection layer, 1023, a third sub-anti-reflection layer. DETAILED DESCRIPTION

[0043] In order to make the technical solutions and advantages in the embodiments of the present application more clearly understood, the exemplary embodiments of the present application are further described in detail below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present application, rather than an exhaustive list of all the embodiments. It should be noted that the embodiments in the present application and the features in the embodiments can be combined with each other without conflict.

[0044] like Figure 1 As shown, this embodiment proposes a chip structure of a GaN-based high-power blue laser, including a substrate 100 and an epitaxial layer 101. The epitaxial layer 101 is arranged on the upper layer of the substrate 100. The left and right sides of the epitaxial layer 101 are respectively a first cavity surface 1011 and a second cavity surface 1012. Among them, the first cavity surface 1011 is located at the far end of the laser emission direction, and the second cavity surface 1012 is located at the near end of the laser emission direction. An anti-reflection layer 102 is plated on the surface of the first cavity surface 1011. A high reflection layer 103 is plated on the surface of the second cavity surface 1012.

[0045] Specifically, in this embodiment, the anti-reflection layer 102 on the surface of the first cavity surface 1011 includes a first sub-anti-reflection layer 1021, a second sub-anti-reflection layer 1022 and a third sub-anti-reflection layer 1023 which are sequentially plated on the surface of the first cavity surface 1011. Figure 2 As shown (this figure is only a schematic diagram and does not represent the actual size). In the structure composed of the epitaxial layer 101 and the anti-reflection layer 102, the electric field intensity of the simulated light field distribution has multiple peak electric field intensities and multiple valley electric field intensities, such as Figure 3 As shown, the specific performance is:

[0046] As for the peak electric field intensity, in this embodiment, there are three peak electric field intensities in total in the epitaxial layer 101 and the anti-reflection layer 102. Among them, the first peak electric field intensity 110 is located in the epitaxial layer 101, the second peak electric field intensity 111 is located in the interface region between the first cavity surface 1011 and the first sub-anti-reflection layer 1021, and the third peak electric field intensity 112 is located in the interface region between the second sub-anti-reflection layer 1022 and the third sub-anti-reflection layer 1023. The first peak electric field intensity 110, the second peak electric field intensity 111 and the third peak electric field intensity 112 have the following relationship:

[0047] The intensity ratio of the first peak electric field intensity 110 to the second peak electric field intensity 111 is 0.8 to 1.2;

[0048] The intensity ratio of the second peak electric field intensity 111 to the third peak electric field intensity 112 is 0.8 to 1.2.

[0049] In general, the first peak electric field strength 110 , the second peak electric field strength 111 and the third peak electric field strength 112 are substantially equivalent.

[0050] As for the valley electric field strength, in this embodiment, there are two valley electric field strengths in total in the epitaxial layer 101 and the anti-reflection layer 102. The first valley electric field strength 120 is located in the epitaxial layer 101, and the second valley electric field strength 121 is located in the first sub-anti-reflection layer 1021. The intensity ratio of the first valley electric field strength 120 to the second valley electric field strength 121 is 0.2 to 0.8.

[0051] In this embodiment, an anti-reflection layer 102 and a high-reflection layer 103 are respectively plated on the cavity surfaces on both sides of the epitaxial layer 101 of the chip structure of the GaN-based high-power blue laser. The anti-reflection layer 102 comprises a first sub-anti-reflection layer 1021, a second sub-anti-reflection layer 1022 and a third sub-anti-reflection layer 1023 which are sequentially plated on the surface of the first cavity surface 1011. The electric field intensity of the simulated optical field distribution of the epitaxial layer 101 and the anti-reflection layer 102 has multiple peak electric field intensities and multiple valley electric field intensities, thereby reducing the laser power density of the anti-reflection layer 102 of the high-power blue laser, reducing the high photon density borne by the laser anti-reflection layer 102 and the high-reflection layer 103, reducing the optical catastrophe probability of the laser, and improving the optical catastrophe current; at the same time, the radiation intensity in the resonant cavity formed by the laser anti-reflection layer 102 and the high-reflection layer 103 decreases, reducing the photon density, and can also reduce the carrier absorption loss of the conduction band and valence band carrier concentration of the active layer, reduce the light absorption loss of impurity defects and Auger recombination, inhibit the Fermi level drift, improve the problem of reducing the state density of the particle number inversion, thereby reducing the threshold current of the laser and improving the photoelectric conversion efficiency of the laser.

[0052] In some optional embodiments, the first sub-anti-reflection layer 1021 is any one of Al2O3, AlN / Al2O3 or AlON / Al2O3, the second sub-anti-reflection layer 1022 is Ta2O5 or SiO2, and the third sub-anti-reflection layer 1023 is Ta2O5 or SiO2.

[0053] Specifically, in this embodiment, the first sub-anti-reflection layer 1021 can be any one of Al2O3, AlN / Al2O3 or AlON / Al2O3. When the first sub-anti-reflection layer 1021 can be Al2O3, the electric field intensity distribution diagram of the simulated light field distribution of the chip structure of the GaN-based high-power blue laser in this embodiment can refer to Figure 3 When the first sub-anti-reflection layer 1021 is AlN / Al2O3 or AlON / Al2O3, the electric field intensity distribution diagram of the simulated light field distribution of the chip structure of the GaN-based high-power blue laser in this embodiment can be referred to Figure 4At this time, the second peak electric field intensity 111 is located at the interface region between the first cavity surface 1011 and the AlN or AlON of the first sub-anti-reflection layer 1021 , and the second valley electric field intensity 121 is located in the Al 2 O 3 of the first sub-anti-reflection layer 1021 .

[0054] In some optional embodiments, the reflectivity of the anti-reflection layer 102 at a laser wavelength of 450 nm is 15% to 30%, and the reflectivity of the high-reflection layer 103 at a laser wavelength of 450 nm is 95% to 100%.

[0055] Different materials have different reflectivities. In this embodiment, when the first sub-anti-reflection layer 1021 is Al2O3, the reflectivity of the anti-reflection layer 102 at a laser wavelength of 450nm is 17%. Figure 5 When the first sub-anti-reflection layer 1021 is AlN / Al2O3 or AlON / Al2O3, the reflectivity of the anti-reflection layer 102 at a laser wavelength of 450nm is 22%. Figure 6 shown.

[0056] For different materials, each material has a refractive index η. The refractive index η is the ratio of the speed of light in a vacuum to the speed of light in a medium. The wavelength of light in a medium is given by the equation λ=λ0 / η, where λ0 is the wavelength of light in a vacuum. Quarter wavelength QWOT=λ0 / 4η is used to determine a quarter wavelength in a layer of a medium. Therefore, in this embodiment, the quarter wavelength QWOT of the first sub-anti-reflection layer 1021, the second sub-anti-reflection layer 1022, and the third sub-anti-reflection layer 1023 made of different materials may also be different.

[0057] Specifically, when the first sub-anti-reflection layer 1021 is Al2O3, the quarter wavelength of the first sub-anti-reflection layer 1021 is 1.8 to 2.2, the quarter wavelength QWOT of the second sub-anti-reflection layer 1022 is 0.01 to 0.2, and the quarter wavelength QWOT of the third sub-anti-reflection layer 1023 is 0.01 to 0.2.

[0058] When the first sub-anti-reflection layer 1021 is AlN / Al2O3 or AlON / Al2O3, the quarter-wavelength QWOT of the AlN or AlON of the first sub-anti-reflection layer 1021 is 0.1 to 0.3, the quarter-wavelength QWOT of the Al2O3 of the first sub-anti-reflection layer 1021 is 1.4 to 1.8, the quarter-wavelength QWOT of the second sub-anti-reflection layer 1022 is 0.1 to 0.3, and the quarter-wavelength QWOT of the third sub-anti-reflection layer 1023 is 0.1 to 0.3.

[0059] Further, when the first sub-anti-reflection layer 1021 is Al2O3, the ratio of the quarter wavelength QWOT of the first sub-anti-reflection layer 1021 to the quarter wavelength QWOT of the second sub-anti-reflection layer 1022 is 20 to 40, the ratio of the quarter wavelength QWOT of the first sub-anti-reflection layer 1021 to the quarter wavelength QWOT of the third sub-anti-reflection layer 1023 is 20 to 40, and the ratio of the quarter wavelength QWOT of the second sub-anti-reflection layer 1022 to the quarter wavelength QWOT of the third sub-anti-reflection layer 1023 is 0.5 to 1.5.

[0060] When the first sub-anti-reflection layer 1021 is AlN / Al2O3 or AlON / Al2O3, the ratio of the quarter-wavelength QWOT of Al2O3 of the first sub-anti-reflection layer 1021 to the quarter-wavelength QWOT of the first sub-anti-reflection layer 1021 is 3 to 20, the ratio of the quarter-wavelength QWOT of Al2O3 of the first sub-anti-reflection layer 1021 to the quarter-wavelength QWOT of the second sub-anti-reflection layer 1022 is 5 to 20, the ratio of the quarter-wavelength QWOT of Al2O3 of the first sub-anti-reflection layer 1021 to the quarter-wavelength QWOT of the third sub-anti-reflection layer 1023 is 5 to 20, and the ratio of the quarter-wavelength QWOT of the second sub-anti-reflection layer 1022 to the quarter-wavelength QWOT of the third sub-anti-reflection layer 1023 is 1 to 3.

[0061] In some optional embodiments, the thicknesses of the first anti-reflection sub-layer 1021 , the second anti-reflection sub-layer 1022 , and the third anti-reflection sub-layer 1023 are also different to a certain extent.

[0062] Specifically, when the first anti-reflection sub-layer 1021 is Al2O3, the thickness of the first anti-reflection sub-layer 1021 is 100nm to 200nm, the thickness of the second anti-reflection sub-layer 1022 is 1nm to 20nm, and the thickness of the third anti-reflection sub-layer 1023 is 1nm to 20nm.

[0063] When the first sub-anti-reflection layer 1021 is AlN / Al2O3 or AlON / Al2O3, the thickness of Al2O3 of the first sub-anti-reflection layer 1021 is 80nm to 150nm, the thickness of AlN or AlON of the first sub-anti-reflection layer 1021 is 5nm to 50nm, the thickness of the second sub-anti-reflection layer 1022 is 1nm to 20nm, and the thickness of the third sub-anti-reflection layer 1023 is 1nm to 20nm.

[0064] Further, when the first sub-anti-reflection layer 1021 is Al2O3, the ratio of the thickness of the first sub-anti-reflection layer 1021 to the thickness of the second sub-anti-reflection layer 1022 is 20 to 50, the ratio of the thickness of the first sub-anti-reflection layer 1021 to the thickness of the third sub-anti-reflection layer 1023 is 20 to 50, and the ratio of the thickness of the second sub-anti-reflection layer 1022 to the thickness of the third sub-anti-reflection layer 1023 is 0.8 to 2.0.

[0065] When the first sub-anti-reflection layer 1021 is AlN / Al2O3 or AlON / Al2O3, the ratio of the thickness of Al2O3 of the first sub-anti-reflection layer 1021 to the thickness of AlN or AlON of the first sub-anti-reflection layer 1021 is 5 to 20, the ratio of the thickness of Al2O3 of the first sub-anti-reflection layer 1021 to the thickness of the second sub-anti-reflection layer 1022 is 5 to 20, the ratio of the thickness of Al2O3 of the first sub-anti-reflection layer 1021 to the thickness of the third sub-anti-reflection layer 1023 is 5 to 20, and the ratio of the thickness of the second sub-anti-reflection layer 1022 to the thickness of the third sub-anti-reflection layer 1023 is 0.8 to 2.0.

[0066] In some optional embodiments, the electric field strength of the epitaxial layer 101 and the anti-reflection layer 102 has a sine or cosine function distribution, such as Figure 3 and Figure 4 shown.

[0067] In some optional embodiments, the number of layers of the anti-reflection layer 102 may also be 4 or 5 layers.

[0068] Specifically, Figure 7 As shown, in this embodiment, the anti-reflection layer 102 has a three-layer structure, and a fourth sub-anti-reflection layer 102 is plated on the outer layer of the third sub-anti-reflection layer 1023. The fourth sub-anti-reflection layer 102 has the same structure as the second sub-anti-reflection layer 1022, that is, the fourth sub-anti-reflection layer 102 is actually the second second sub-anti-reflection layer 1022, so as to form an anti-reflection layer 102 with a four-layer structure.

[0069] like Figure 8 As shown. Based on the structure of the four-layer anti-reflection layer 102, a fifth sub-anti-reflection layer 102 can be plated on the outer layer of the fourth sub-anti-reflection layer 102. The fifth sub-anti-reflection layer 102 has the same structure as the third sub-anti-reflection layer 1023, that is, the fifth sub-anti-reflection layer 102 is actually the second layer of the third sub-anti-reflection layer 1023, so as to form a five-layer anti-reflection layer 102.

[0070] In some optional embodiments, the epitaxial layer 101 includes a lower confinement layer, a lower waveguide layer, an active layer, an upper waveguide layer, an electron blocking layer and an upper confinement layer arranged in sequence from bottom to top, such as Fig. 9The epitaxial layer 101 is any one or any combination of GaN, InGaN, InN, AlInN, AlGaN, AlInGaN, AlN, GaAs, GaP, InP, AlGaAs, AlInGaAs, AlGaInP, InGaAs, InGaAsN, AlInAs, AlInP, AlGaP, InGaP, GaSb, InSb, InAs, InAsSb, AlGaSb, AlSb, InGaSb, AlGaAsSb, InGaAsSb, SiC, Ga2O3, BN, and diamond.

[0071] In some optional embodiments, the substrate 100 includes sapphire, silicon, Ge, SiC, AlN, GaN, GaAs, InP, InAs, GaSb, sapphire / SiO2 composite substrate, Mo, TiW, CuW, Cu, sapphire / AlN composite substrate, diamond, graphene, sapphire / SiN x , Sapphire / SiO2 / SiN x Composite substrate, sapphire / SiN x Any one of a / SiO2 composite substrate, a magnesium aluminum spinel MgAl2O4, MgO, ZnO, ZrB2, LiAlO2 and LiGaO2 composite substrate.

[0072] The following table is a parameter comparison of the chip structure of a conventional semiconductor laser chip and the GaN-based high-power blue laser proposed in this embodiment, including optical catastrophe ratio, optical catastrophe current, optical power, photoelectric conversion efficiency and threshold current, showing the difference between the chip structure of a conventional semiconductor laser chip and the GaN-based high-power blue laser proposed in this embodiment:

[0073]

[0074] It can be seen that the chip structure of the GaN-based high-power blue laser proposed in this embodiment improves the optical catastrophe current, optical power and photoelectric conversion efficiency, reduces the optical catastrophe ratio and threshold current compared with traditional semiconductor laser chips, and has obvious advantages over traditional semiconductor laser chips.

[0075] Obviously, those skilled in the art can make various changes and modifications to the present application without departing from the spirit and scope of the present application. Thus, if these modifications and variations of the present application fall within the scope of the claims of the present application and their equivalents, the present application is also intended to include these modifications and variations.

Claims

1. A GaN-based high-power blue laser chip structure, comprising a substrate and an epitaxial layer, wherein the epitaxial layer is arranged on the upper layer of the substrate, characterized in that: The left and right sides of the epitaxial layer are respectively a first cavity surface and a second cavity surface, and the first cavity surface is located at the far end of the laser emission direction, and the second cavity surface is located at the near end of the laser emission direction, the surface of the first cavity surface is plated with an anti-reflection layer, and the surface of the second cavity surface is plated with a high reflection layer, and the anti-reflection layer includes a first sub-anti-reflection layer, a second sub-anti-reflection layer and a third sub-anti-reflection layer sequentially plated on the surface of the first cavity surface, and the electric field intensity of the simulated light field distribution of the epitaxial layer and the anti-reflection layer has multiple peak electric field intensities and multiple valley electric field intensities; The first peak electric field intensity is located in the epitaxial layer, the second peak electric field intensity is located in the interface region between the first cavity surface and the first sub-anti-reflection layer, the third peak electric field intensity is located in the interface region between the second sub-anti-reflection layer and the third sub-anti-reflection layer, the intensity ratio of the first peak electric field intensity to the second peak electric field intensity is 0.8 to 1.2, and the intensity ratio of the second peak electric field intensity to the third peak electric field intensity is 0.8 to 1.2; The first valley electric field strength is located in the epitaxial layer, the second valley electric field strength is located in the first sub-anti-reflection layer, and the intensity ratio of the first valley electric field strength to the second valley electric field strength is 0.2 to 0.

8.

2. The chip structure of the GaN-based high-power blue laser according to claim 1, characterized in that: The reflectivity of the anti-reflection layer is 15% to 30% when the laser wavelength is 450nm, and the reflectivity of the high-reflection layer is 95% to 100% when the laser wavelength is 450nm.

3. The chip structure of the GaN-based high-power blue laser according to claim 1, characterized in that: The first sub-anti-reflection layer is any one of Al2O3, AlN / Al2O3 or AlON / Al2O3, the second sub-anti-reflection layer is Ta2O5 or SiO2, and the third sub-anti-reflection layer is Ta2O5 or SiO2.

4. The chip structure of the GaN-based high-power blue laser according to claim 3, characterized in that: When the first sub-anti-reflection layer is Al2O3, the quarter wavelength of the first sub-anti-reflection layer is 1.8 to 2.2, the quarter wavelength of the second sub-anti-reflection layer is 0.01 to 0.2, and the quarter wavelength of the third sub-anti-reflection layer is 0.01 to 0.2; When the first sub-anti-reflection layer is AlN / Al2O3 or AlON / Al2O3, the quarter wavelength of AlN or AlON of the first sub-anti-reflection layer is 0.1 to 0.3, the quarter wavelength of Al2O3 of the first sub-anti-reflection layer is 1.4 to 1.8, the quarter wavelength of the second sub-anti-reflection layer is 0.1 to 0.3, and the quarter wavelength of the third sub-anti-reflection layer is 0.1 to 0.

3.

5. The chip structure of the GaN-based high-power blue laser according to claim 4, characterized in that: When the first sub-anti-reflection layer is Al2O3, the ratio of a quarter wavelength of the first sub-anti-reflection layer to a quarter wavelength of the second sub-anti-reflection layer is 20 to 40, the ratio of a quarter wavelength of the first sub-anti-reflection layer to a quarter wavelength of the third sub-anti-reflection layer is 20 to 40, and the ratio of a quarter wavelength of the second sub-anti-reflection layer to a quarter wavelength of the third sub-anti-reflection layer is 0.5 to 1.5; When the first sub-anti-reflection layer is AlN / Al2O3 or AlON / Al2O3, the ratio of one-quarter wavelength of Al2O3 in the first sub-anti-reflection layer to one-quarter wavelength of the first sub-anti-reflection layer is 3 to 20, the ratio of one-quarter wavelength of Al2O3 in the first sub-anti-reflection layer to one-quarter wavelength of the second sub-anti-reflection layer is 5 to 20, the ratio of one-quarter wavelength of Al2O3 in the first sub-anti-reflection layer to one-quarter wavelength of the third sub-anti-reflection layer is 5 to 20, and the ratio of one-quarter wavelength of the second sub-anti-reflection layer to one-quarter wavelength of the third sub-anti-reflection layer is 1 to 3.

6. The chip structure of the GaN-based high-power blue laser according to claim 3, characterized in that: When the first sub-anti-reflection layer is Al2O3, the thickness of the first sub-anti-reflection layer is 100nm to 200nm, the thickness of the second sub-anti-reflection layer is 1nm to 20nm, and the thickness of the third sub-anti-reflection layer is 1nm to 20nm; When the first sub-anti-reflection layer is AlN / Al2O3 or AlON / Al2O3, the thickness of Al2O3 of the first sub-anti-reflection layer is 80nm to 150nm, the thickness of AlN or AlON of the first sub-anti-reflection layer is 5nm to 50nm, the thickness of the second sub-anti-reflection layer is 1nm to 20nm, and the thickness of the third sub-anti-reflection layer is 1nm to 20nm.

7. The chip structure of the GaN-based high-power blue laser according to claim 6, characterized in that: When the first sub-anti-reflection layer is Al2O3, the thickness ratio of the first sub-anti-reflection layer to the second sub-anti-reflection layer is 20 to 50, the thickness ratio of the first sub-anti-reflection layer to the third sub-anti-reflection layer is 20 to 50, and the thickness ratio of the second sub-anti-reflection layer to the third sub-anti-reflection layer is 0.8 to 2.0; When the first sub-anti-reflection layer is AlN / Al2O3 or AlON / Al2O3, the ratio of the thickness of Al2O3 in the first sub-anti-reflection layer to the thickness of the first sub-anti-reflection layer AlN or AlON is 5 to 20, the ratio of the thickness of Al2O3 in the first sub-anti-reflection layer to the thickness of the second sub-anti-reflection layer is 5 to 20, the ratio of the thickness of Al2O3 in the first sub-anti-reflection layer to the thickness of the third sub-anti-reflection layer is 5 to 20, and the ratio of the thickness of the second sub-anti-reflection layer to the thickness of the third sub-anti-reflection layer is 0.8 to 2.

0.

8. The chip structure of the GaN-based high-power blue laser according to claim 1, characterized in that: The electric field strength of the epitaxial layer and the anti-reflection layer has a sine or cosine function distribution.

9. The chip structure of the GaN-based high-power blue laser according to claim 1, characterized in that: The outer layer of the third sub-anti-reflection layer is also plated with a fourth sub-anti-reflection layer, and the fourth sub-anti-reflection layer has the same structure and composition as the second sub-anti-reflection layer; Alternatively, the outer layer of the third sub-anti-reflection layer is also sequentially plated with a fourth sub-anti-reflection layer and a fifth sub-anti-reflection layer, the fourth sub-anti-reflection layer has the same structural composition as the second sub-anti-reflection layer, and the fifth sub-anti-reflection layer has the same structural composition as the third sub-anti-reflection layer.

10. The chip structure of the GaN-based high-power blue laser according to claim 1, characterized in that: The epitaxial layer comprises a lower confinement layer, a lower waveguide layer, an active layer, an upper waveguide layer, an electron blocking layer and an upper confinement layer which are sequentially arranged from bottom to top, and the epitaxial layer is any one or any combination of GaN, InGaN, InN, AlInN, AlGaN, AlInGaN, AlN, GaAs, GaP, InP, AlGaAs, AlInGaAs, AlGaInP, InGaAs, InGaAsN, AlInAs, AlInP, AlGaP, InGaP, GaSb, InSb, InAs, InAsSb, AlGaSb, AlSb, InGaSb, AlGaAsSb, InGaAsSb, SiC, Ga2O3, BN and diamond; The substrate includes sapphire, silicon, Ge, SiC, AlN, GaN, GaAs, InP, InAs, GaSb, sapphire / SiO2 composite substrate, Mo, TiW, CuW, Cu, sapphire / AlN composite substrate, diamond, graphene, sapphire / SiN x , Sapphire / SiO2 / SiN x Composite substrate, sapphire / SiN x Any one of a / SiO2 composite substrate, a magnesium aluminum spinel MgAl2O4, MgO, ZnO, ZrB2, LiAlO2 and LiGaO2 composite substrate.